PERAN PENDIDIKAN PESANTREN DALAM PEMBENTUKAN KARAKTER STUDI KASUS PONDOK PESANTREN ILMU AL-QUR’AN (PIQ) SINGOSARI MALANG - Kholilur Rohman; Adi Sudrajat (VICRATINA, 2020)
First of all this article discusses broadly, about the pattern of kakrakter education in the Islamic Boarding School of the Al-Qur'an Singosari Malang. Second, the method used in character education. Then the last is the implementation of the application of the characters produced by the Islamic Boarding School of the Qur'an (PIQ). These three problems arise to find out about character education in Islamic boarding schools. This can be demonstrated by the diverse behavior of students in daily life, which from this character education can determine the success or failure of students when leaving a boarding school. This study uses a qualitative descriptive method by which researchers collect data through researchers' observations in the field based on the theories and ideas of experts. The conclusion of this study is the character education in the Islamic Boarding School of the Qur'an (PIQ) in the form of habitual daily positive things shows that students are indirectly accustomed to positive things so that the inculcation of characters like this can be inherent in the students Pesntren Qur'anic Sciences (PIQ).